2022
DOI: 10.1112/blms.12607
|View full text |Cite
|
Sign up to set email alerts
|

On Stein rational balls smoothly but not symplectically embedded in CP2$\mathbb {CP}^2$

Abstract: We extend recent work of Brendan Owens by constructing a doubly infinite family of Stein rational homology balls which can be smoothly but not symplectically embedded in ℂℙ 2 . M S C ( 2 0 2 0 ) 57R40 (primary), 57K43, 57R17 (secondary)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Remark 1.5. In [11] we constructed infinitely many embeddings B p,q → CP 2 , extending a family of embeddings constructed by Owens [13]. It is not hard to check that our constructions implicitely used horizontal decompositions of CP 2 -in fact, those constructions led us to the discovery of horizontal decompositions.…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…Remark 1.5. In [11] we constructed infinitely many embeddings B p,q → CP 2 , extending a family of embeddings constructed by Owens [13]. It is not hard to check that our constructions implicitely used horizontal decompositions of CP 2 -in fact, those constructions led us to the discovery of horizontal decompositions.…”
mentioning
confidence: 93%
“…Owens [13] showed that infinitely many B p,q 's admit smooth embeddings in CP 2 but by [2] they cannot be symplectically embedded. The authors extended Owens' family [11] and proved the non-existence of almost complex embeddings [10] without relying on [2]. The present paper is a natural continuation of [12], where we introduced certain handlebody decompositions that we call horizontal, classified the closed 4-manifolds with the simplest horizontal decompositions and in doing so we recovered infinitely many of the known smooth embeddings B p,q → CP 2 .This paper consists of two parts.…”
mentioning
confidence: 96%
See 1 more Smart Citation